Speed testing in foil and epee fencers during specific attacks - Weichenberger, M.; Steegmueller, W.; Steinacker, J. M. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The speed during fencing attacks is considered to be very important for success in competition. It is assumed that foil fencers move faster than epee fencers, but the speed during specific attacks has not been analyzed before. The aim of our study was to compare movement speed and reaction time during specific fencing attacks in foil and epée fencers. Methods: 9 male epée fencers (EPEE, 15.6 ± 0.5 yrs, 72.2 ± 9.8 kg, 181.0 ± 7.0 cm) and 8 foil fencers (FOIL, 16.3 ± 1.6 yrs, 76.2 ± 8.8 kg, 179.9 ± 5.1 cm) of the German national junior team took part in the study. The measurements were focused on speed of the weapon hand during the fencing attacks touch (TOU), lunge (LUN), step forward lunge (SFL) and flèche (FLE). An optical motion capture system (2000 Hz, Lukotronic, Austria) with 16 active infrared markers was used to analyze speed and technique during the attacks. A fencing dummy with target areas was integrated into the system for detecting reaction time (RTIME). The study participants performed 5 trials for every fencing attack. During attacks, mean speed (MEANSPD), maximum speed (MAXSPD), time to reach maximum speed (TMAXSPD) and speed in the moment of hit (HITSPD) were measured. Results: FOIL had greater MEANSPD and MAXSPD during TOU (1.23 ± 0.33m/s, 2.25 ± 0.44m/s), LUN (1.86 ± 0.28m/s, 3.26 ± 0.39m/s) and SFL (2.03 ± 0.15m/s, 3.83 ± 0.56m/s) than EPEE (TOU: 1.05 ± 0.33m/s, 1.85 ± 0.65m/s; LUN: 1.76 ± 0.19m/s, 3.18 ± 0.31m/s; SFL: 1.92 ± 0.21m/s, 3.56 ± 0.63m/s, p< .05). MAXSPD for FLE was higher in EPEE (3.65 ± 0.60m/s) than in FOIL (3.39 ± 0.31m/s, p< .05). TMAXSPD in FOIL during LUN and SFL was greater than in EPEE (0.40 ± 0.06s vs. 0.46 ± 0.08s; 0.78 ± 0.08s vs. 0.95 ± 0.08s). HITSPD during TOU (1.56 ± 0.40m/s vs. 1.25 ± 0.65m/s), LUN (2.52 ± 0.58m/s vs. 2.21 ± 0.44m/s) and SFL (3.06 ± 0.82m/s vs. 2.57 ± 0.53m/s) was greater in FOIL. RTIME for LUN and SFL was better in EPEE than in FOIL (0.21 ± 0.05s vs. 0.24 ± 0.05s and 0.22 ± 0.05s vs. 0.26 ± 0.04s, p< .05) but there were no differences for TOU and FLE. Discussion: The newly developed fencing-specific method and the described speed parameters are suitable to analyze movement speed and reaction time during fencing attacks. Data confirm the assumption that foil fencers generally move faster than epée fencers. The slower reaction times of foil fencers during LUN and SFL can be explained by the fact that foil fencers start these attacks, in contrast to epee, with the lower limbs. These differences are most likely due to different competition rules and should be considered during reaction tests in fencing.